The Effectiveness Of Salicylic acid Therapy In Mild and Moderate Acne Vulgaris - Nafila, Alfin; Nursanto, Dodik; Sintowati, Retno; Pramuningtyas, Ratih (MAGNA MEDICA Berkala Ilmiah Kedokteran dan Kesehatan, 2024)
Background: Acne vulgaris is a chronic inflammatory disease of polysebaceous follicles characterized by lesions that include blackheads, papules, pustules, nodules, and cysts. The prevalence of acne vulgaris is most significant among adolescents aged 15 to 18. In mild and moderate acne vulgaris, topical treatment enhances skin conditions. It is believed that the ability of salicylic acid to reach the stratum corneum, which exfoliates due to its comedolytic properties, aids in the healing of acne vulgaris.Objective: Evaluate the efficacy of salicylic acid as a treatment for mild and moderate acne vulgaris.Methods: This study's design involved a literature search using the terms acne vulgaris and salicylic acid in Google Scholar, PubMed, and Science Direct.Results: The investigation found 108 articles were discovered and excluded based on the restriction criteria; 8 articles were reviewed. Salicylic acid substantially improved mild and moderate acne, according to all studies. Improvement was measured based on the lesion's severity, the lesion type, and Goodman's qualitative global scarring grading system. There is an improvement in inflammatory, non-inflammatory, and hyperpigmented lesions.Conclusion: Salicylic acid is clinically beneficial for mild to moderate acne vulgaris.